Dynamics of educational activity of students under the influence of digitalisation - D. Yu. Narkhov; E. N. Narkhova; D. V. Shkurin (Russian State Vocational Pedagogical University, 2021)
Introduction. The relevance of the study is due to the aggravation of the complex of student problems caused by the sharp acceleration of digitalisation and the destruction of the established complex of social interactions under the influence of the COVID-19 pandemic, both within the student community, and between the student body and other educational communities. The fixation of qualitative changes in educational activity in non-standard conditions, along with the development of a theoretical basis for the digital educational community of students, is necessary for making qualified managerial decisions.The aim of the present research was to identify the factors and dynamics of students as a digital educational community in the context of self-isolation and online learning.Methodology and research methods. This study is based on the use of specific approaches to industry-specific sociological knowledge (youth and education): community, system, structural-functional, institutional, temporal, thesaurus, network, panoramic (pedagogical science). The current research employs the results of a mass survey conducted among students (N = 1825, 19 universities of the Sverdlovsk region) according to the authors' method. A mixed survey was carried out through a representative quota-target sample using traditional and electronic forms, implemented on the CAWI (Computer Assisted Web Interview) platform. Data processing was implemented using the VORTEX application package. Data verification was carried out using materials from the secondary data analysis of the VII stage of the regional student survey in 2016.Results. In the course of the study, the general forming characteristics of traditional, virtual and digital educational communities of students were clarified. The transition from traditional to digital community has been fixed. The key terms of the educational community of students in the digital age were defined. The indicators of educational activity were identified and investigated: effect of self-isolation regime on educational activity, features of online education, dynamics of the educational time budget, self-assessment of knowledge gained online, etc. The factors that determine educational activity were examined: motivation, sources of information, material and technical support, and organisational and technological consulting. On the basis of empirical materials, qualitative changes in the importance of digital information and digital material and technological support for successful studying were revealed. Insufficient digital competence of students is shown. Positive and negative aspects of online education were revealed, including under the influence of physical and psychological changes associated with the regime of complete self-isolation. The main reason for the desire of students to continue their education in a traditional or mixed form is substantiated - a decrease in the quality of education due to the exacerbation of the contradiction between the classical university and "everyday digital" educational culture.Scientific novelty lies in the development of the concept of the digital educational community of students, concretisation of its general-forming characteristics, clarification of the terminological range of the digital community and the educational activity of students; obtaining and systematising new empirical information about the state of students in the Sverdlovsk region as a major scientific and educational region of the country.Practical significance. The materials obtained provide grounds for clarifying the process and results of digitalisation of the educational space, assessing the state of the student community in extraordinary conditions of self-isolation and learning experience in a full online learning mode. Developed tools can be applied for further monitoring student learning. The obtained quantitative data can be used for the advancement of teaching and learning in digital and mixed formats, as well as for scientific substantiation of management decisions.